Adverse effects of cell phone radiation on Purkinje cells of the cerebellum of pregnant Balb/c mice - Armalina, Desy; Susilaningsih , Neni; Sutanto, Heri; Sunarno, Sunarno (Faculty of Medicine, Universitas Islam Indonesia, 2026)
Background: Pregnant women often use mobile phones for communication and health-related information. The World Health Organization (WHO) recommends minimizing mobile phone use during pregnancy to reduce maternal and child health risks. Electromagnetic waves (EMW) from cell phones can be absorbed by the brain and may affect neuronal function.Objective: This study aimed to evaluate the size, histology, and number of Purkinje cells in the cerebellum of pregnant mice exposed to cell phone EMW compared to unexposed controls.Methods: Fourteen pregnant Balb/c mice were randomly divided into exposed (EG) and control (CG) groups. The EG was exposed to an electromagnetic wave with a specific absorption rate (SAR) of 1.74 W/kg for 24 hours per day from gestation day 0 to 19. On day 20, cerebellar tissues were harvested and processed with hematoxylin–eosin (HE) staining for histological assessment.Results: The mean Purkinje cell size in the EG (0.069 ± 0.009 mm) was slightly smaller than in the CG (0.070 ± 0.007 mm), but this difference was not statistically significant (p = 0.741). However, the Purkinje cell count was significantly lower in the EG (6.160 ± 0.746) than in the CG (7.800 ± 0.764; p < 0.001), indicating that EMW exposure reduced Purkinje cell numbers.Conclusion: Exposure to cell phone EMW during pregnancy led to a significant reduction in Purkinje cell numbers in the cerebellum, while cell size remained unchanged. These findings suggest that prenatal exposure to EMW may negatively affect fetal cerebellar development. This underscores the need for pregnant women to be cautious with mobile phone use and highlights the importance of further research to clarify the risks to maternal and fetal health.